Prevalence of coronary artery calcification in a non-specific chest pain population in emergency and cardiology departments compared with the background population: a prospective cohort study in Southern Denmark with 12-month follow-up of cardiac endpoints. Issue 3 (3rd March 2018) - Ilangkovan, Nivethitha; Mogensen, Christian Backer; Mickley, Hans; Lassen, Annmarie Touborg; Lambrechtsen, Jess; Sand, Niels Peter Ronnow; Albiniussen, Rasmus; Byg, Jørgen; Hald, Flemming; Grønhøj, Mette Hjortdal; Diederichsen, Axel
Abstract : Objectives: To examine and compare the prevalence of coronary artery calcification (CAC) and the frequency of cardiac events in a background population and a cohort of patients with non-specific chest pain (NSCP) who present to an emergency or cardiology department and are discharged without an obvious reason for their symptom. Design: A double-blinded, prospective, observational cohort study that measures both CT-determined CAC scores and cardiac events after 1 year of follow-up. Setting: Emergency and cardiology departments in the Region of Southern Denmark. Subjects: In total, 229 patients with NSCP were compared with 722 patients from a background comparator population. Main outcomes measures: Prevalence of CAC and incidence of unstable angina (UAP), acute myocardial infarction (MI), ventricular tachycardia (VT), coronary revascularisation and cardiac-related mortality 1 year after index contact. Results: There was no significant difference in the prevalence of CAC (OR 0.9 (95% CI 0.6 to 1.3), P=0.546) or the frequency of cardiac endpoints (P=0.64) between the studied groups. When compared with the background population, the OR for patients with NSCP for a CAC >100 Agatston units (AU) was 1.0 (95% CI 0.6 to 1.5), P=0.826. During 1 year of follow-up, two (0.9%) patients with NSCP underwent cardiac revascularisation, while none experienced UAP, MI, VT or death. In the background population, four (0.6%) participants experienced a clinical cardiac endpoint; two had an MI, one had VT and one had a cardiac-related death. Conclusion: The prevalence of CAC (CAC >0 AU) among patients with NSCP is comparable to a background population and there is a low risk of a cardiac event in the first year after discharge. A CAC study does not provide notable clinical utility for risk-stratifying patients with NSCP. Trial registration number: NCT02422316 ; Pre-results.